2.4GHz Wi-Fi Analyzer - MOHAMMED MAIDIN, MUHAMMAD KHAIRUL AMIZUL; Bahari, Azlina (Progress in Engineering Application and Technology, 2023)
Wi-Fi enables computers, tablets, cellphones, and other devices to connect wirelessly and with the internet. Wi-Fi is a wireless router’s radio transmission to a nearby device. The gadget turns signal data into usable data. Wi-Fi analyzers examine the connection, collect essential data, and determine the cause of a weak Wi-Fi signal. Wi-Fi analyzers collect data from your network’s access points and channels and present it in visual reports and dashboards. 2.4GHz Wi-Fi Analyzer is created using Eclipse IDE, Android Studio, Java, and Kotlin. The OOSD method is used to construct this application. 2.4GHz Wi-Fi analyzer will provide channel graph, time graph, and nearby access points.